ANALISIS HUKUM PERLINDUNGAN HAK CIPTA TERHADAP KARYA YANG DICIPTAKAN OLEH KECERDASAN BUATAN - Wandi Kaunang, Prishela; Novy Tuwaidan, Arthur; Aryani Manangin, Susi (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
Intellectual Property Rights (IPR) play a crucial role in both regional and international trade. Indonesia has ratified the Uruguay Round Agreement through Law No. 7 of 1994, which includes provisions on the protection of copyright as one of the key aspects of IPR. This study uses a normative legal research method, employing statutory and conceptual approaches to analyze the copyright status of AI-generated works under Indonesian law. The results show that Indonesian copyright protection requires works to have originality, be expressed in a tangible form, and be the product of human creativity. Since AI lacks consciousness and intentionality, its creations do not meet the subjective requirement of authorship. However, these works often satisfy the objective criteria of copyrightable works. Comparative legal analysis with systems in the European Union and the United Kingdom highlights differing views—while the EU requires human intellectual input for copyright protection, UK law allows computer-generated works to be protected under certain conditions. In the long term, legal reform is necessary to accommodate AI-generated works, ensuring legal certainty and fairness in the digital age. A suitable regulatory framework must be developed to adapt the concept of